2018
DOI: 10.1088/1361-648x/aad24f
|View full text |Cite
|
Sign up to set email alerts
|

Water-induced reordering in ultrathin ionic liquid films

Abstract: Water-induced reordering in ultrathin ionic liquid films has been observed using in situ x-ray photoelectron spectroscopy. An ultrathin layer of 1-butyl-3-methylimidazolium tetrafluoroborate ([CCIm][BF]) was deposited on a rutile TiO (1 1 0) single crystal and exposed to water vapour at a relative humidity of ~70% in an in situ cell. Water was found to adsorb onto the ionic liquid surface, causing a reordering of the ions at the interface. Water initially remained trapped on the ionic liquid surface as the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 42 publications
(64 reference statements)
4
15
0
Order By: Relevance
“…Rivera-Rubero and Baldelli, for example, showed that water can be removed from the IL 1-butyl-3-methylimidazolium tetrafluoroborate ([C 4 C 1 Im]­[BF 4 ]) at pressures of <1 × 10 –5 mbar at room temperature . The recent availability of near-ambient pressure XPS (NAPXPS) has opened up the possibility of measurements of liquid surfaces in gas pressures of up to a few tens of mbar. ,, In our own work and in works of groups such as the Newberg group, NAPXPS has allowed for surface-sensitive studies of the interactions between gas molecules and ILs. Herein, we examine the reaction of the superbasic IL, [P 66614 ]­[benzim], with CO 2 , H 2 O, and two mixed CO 2 /H 2 O vapor regimes using NAPXPS.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Rivera-Rubero and Baldelli, for example, showed that water can be removed from the IL 1-butyl-3-methylimidazolium tetrafluoroborate ([C 4 C 1 Im]­[BF 4 ]) at pressures of <1 × 10 –5 mbar at room temperature . The recent availability of near-ambient pressure XPS (NAPXPS) has opened up the possibility of measurements of liquid surfaces in gas pressures of up to a few tens of mbar. ,, In our own work and in works of groups such as the Newberg group, NAPXPS has allowed for surface-sensitive studies of the interactions between gas molecules and ILs. Herein, we examine the reaction of the superbasic IL, [P 66614 ]­[benzim], with CO 2 , H 2 O, and two mixed CO 2 /H 2 O vapor regimes using NAPXPS.…”
Section: Introductionmentioning
confidence: 90%
“…20 The recent availability of near-ambient pressure XPS (NAPXPS) has opened up the possibility of measurements of liquid surfaces in gas pressures of up to a few tens of mbar. 4,8,21−23 In our own work 24 and in works of groups such as the Newberg group, 25−27…”
Section: ■ Introductionmentioning
confidence: 98%
“…TiO 2 is a representative photoanode material in DSSCs, and the IL–TiO 2 interface is of particular interest in DSSC research as detailed knowledge of interfacial structures may shed light on device differences in regard to function and durability . A combination of XPS and extended X-ray absorption fine structure spectra showed that [C 4 MIM]­[BF 4 ] absorbs onto the anatase(101) surface, the most thermodynamically stable and dominant surface exposed in the TiO 2 substrate, in an ordering manner via electrostatic interactions at a low coverage with imidizolium rings oriented at 32 ± 4° from the anatase surface. , With an increase in coverage of [C 4 MIM]­[BF 4 ] on the anatase(101) surface, the influence of the TiO 2 surface on interfacial orientations of confined ions at the uppermost IL–vapor layers is reduced and interfacial ordering structures are partially or totally lost. Above specific temperatures, both cations and anions undergo surface-induced degradation on the anatase(101) surface, leading to a production of varied ion species detected by XPS. , The decomposition mechanism of ILs on the anatase(101) surface is distinct depending on ion structures and temperatures.…”
Section: Ionic Liquids In Interfacial Regionsmentioning
confidence: 99%
“…The surface structure of IL thin and thick films has previously been explored by using a variety of different substrates including metals (Au, , Ag, Cu, , and Pt), metal oxides (TiO 2 , , ZnO), carbon (graphite, graphene, and nanotubes), and many more. We opted to study rutile TiO 2 (110) as our substrate for its relevance in a wide range of IL-based technologies including catalysts, TiO 2 nanotubes, and photovoltaic devices. Modification of these systems using ILs can lead to greener technologies with improved performance and stability. ,, …”
Section: Resultsmentioning
confidence: 99%